2007
DOI: 10.1253/circj.71.1728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Menopause on the Myocardial Velocities and Myocardial Performance Index

Abstract: enopause is a critical period in a woman's life, during which many physiologic and pathologic changes occur. Women spend one-third of their lifetime in this period and the hormonal changes that occur during this period have significant influences on several organs and systems. The cardiovascular system is among the most dramatically affected systems. Changes in cardiovascular risk factors due to estrogen deficiency and subsequent increase in cardiovascular morbidity and mortality have been demonstrated in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…In order to minimize bias, echocardiograms of both menopausal and premenopausal groups were performed by cardiologists blinded to the clinical data. In addition, this subclinical impairment in the myocardial functions shows a similarity with the previous studies performed with conventional imaging methods . Our study results demonstrate that LV functions may be impaired with the development of menopause, even in cases where conventional imaging methods do not show any difference.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In order to minimize bias, echocardiograms of both menopausal and premenopausal groups were performed by cardiologists blinded to the clinical data. In addition, this subclinical impairment in the myocardial functions shows a similarity with the previous studies performed with conventional imaging methods . Our study results demonstrate that LV functions may be impaired with the development of menopause, even in cases where conventional imaging methods do not show any difference.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, studies have shown that menopause, characterized by markedly decreased levels of estrogen, leads to significant increases in cardiovascular mortality and morbidity . Although there are many studies focusing on the relationship between menopause and adverse cardiovascular events, the published work on cardiac structure and function is comprised of only a few studies . In these few studies, menopause has been shown to have an impact on cardiovascular structure and functions, however, these studies appear to have many limitations such as different age groups and lack of advanced echocardiography techniques.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the patients with diabetes mellitus were excluded from the study. Furthermore, females were excluded due to negative effects of menopause and ovulation phases on LV MPI . Another major limitation was lack of myocardial blush grading (MBG).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Furthermore, females were excluded due to negative effects of menopause and ovulation phases on LV MPI. 53 Another major limitation was lack of myocardial blush grading (MBG). Longer angiographic records and optimal opaque injection are required to obtain reliable angiographic views to assess MBG.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Furthermore, changes have been observed in the structure and cardiac tissue as a result of pathological hypertrophy and increased fibrosis (1,9,22,55,76). All of these changes seem to contribute to the development of cardiac dysfunction, which is often observed in experimental and clinical studies (2,12,23,31,43,53).…”
mentioning
confidence: 99%